Comparison of two different doses dexmedetomidine as an adjuvant to bupivacaine in sub-arachnoid block for abdominal hysterectomies. A randomized double blinded study. - Prabhu, R Krishna; Radhakrishnan, A (Asian Journal of Medical Sciences, 2017)
Background: Abdominal hysterectomy is often a long duration procedure and warrants intense pain relief in the post-operative period. Dexmedetomidine when added to bupivacaine in subarachnoid block prolongs the duration of surgical anaesthesia, decreases blood loss and prolongs duration of post-operative pain relief. Aims and Objective: To compare two different doses dexmedetomidine as an adjuvant to bupivacaine in sub-arachnoid block in abdominal hysterectomy surgeries. Materials and Methods: 60 patients of age group 30-60 years posted for elective abdominal hysterectomies under American Society of Anaesthesiologists (ASA) physical classification I or II were randomly allocated into 2 groups of 30 each. Group A received 5 micrograms (μg) of dexmedetomidine along with 3.5 ml of 0.5% bupivacaine in sub-arachnoid block. Group B received 10 μg of dexmedetomidine along with 3.5 ml of 0.5% bupivacaine in sub-arachnoid block. Changes in blood pressure, heart rate, respiratory rate, oxygen saturation, ephedrine consumption, blood loss, duration of sensory block, duration of motor block, duration of analgesia were compared between two groups. Results: There was no significant difference in change in heart rate, respiratory rate, oxygen saturation, duration of sensory block, duration of motor block between two groups. Patients in group B had significant decrease in blood pressure, blood loss and significant increase in ephedrine consumption compared to Group A. The duration of analgesia was also prolonged in group B compared to Group A. Conclusion: Dexmedetomidine in dose of 10 μg is a better adjuvant to bupivacaine for abdominal hysterectomy surgeries. Asian Journal of Medical Sciences Vol.8(2) 2017 59-63